Sherlock Holmes: Whose Tissue Is It Anyway?. (October 2020) - Lee, Bonita; Silverman, Jason; Lacson, Atilano; Izevbaye, Iyare; Huynh, Hien; Sergi, Consolato; Maglantay, Remegio; Mather, Cheryl; Box, Adrian; Paonessa, Teresa; Nawaz, Rebecca; Pulongbarit, Jesusa; et al.
Abstract : Background: The medical device reprocessing department (MDRD) is a crucial patient safety area with checkpoints to ensure appropriate reprocessing. Objective: We report the application of molecular pathology in the investigation of potential blood and body fluid exposure (BBFE) during endoscopy. Methods: When there is a potential BBFE from a medical device, our hospital has a systematic process whereby the clinical area involves the MDRD and the infection prevention control (IPC) team. The MDRD provides reprocessing documentation, including detailed information regarding the prior use of the devices. The clinician and the IPC physician discuss the risk of BBFE. If patient disclosure occurs, the IPC physician provides follow-up as appropriate. This report illustrates the collaboration of clinicians, the IPC team, the MDRD, pathologists, and molecular pathologists in investigating the possibility of residual human tissue and BBFE during endoscopy. Case reports: Two independent but similar events occurred in September 2016 and September 2019 in the pediatric endoscopy suite at our site, a tertiary-care pediatric hospital with 163 beds in Edmonton, Canada. During both endoscopies, the pediatric gastroenterologists observed a piece of tissue ejected from the gastroscope into the intestinal lumen when the biopsy forceps were pushed out of the channel for the first time. This observation raised concerns of possible gaps in the reprocessing of the endoscope and residual tissue remaining in the working channel after its last use. Both gastroenterologists were able to retrieve the presumed foreign tissue; however, both patients had possible BBFE because the mucosal surface was breached by the biopsy forceps. The MDRD reprocessing of both endoscopes was reviewed, and no gap was identified. In discussion with the pathologists and molecular pathologists, human identity testing using genetic markers was performed on the biopsy blocks of the previous patient on whom the endoscope was used, the potentially exposed patient, and the presumed foreign tissue for each event. The test results indicated that the presumed foreign tissue was in fact from the potentially exposed patient and therefore there was no BBFE. It is presumed that the working channel itself captured a small amount of the patient's tissue during scope insertion. The results were a relief to the patients and families. Conclusions: It is prudent to investigate residual foreign tissue in a medical device that is being used on patients with mucosal breaches. Molecular pathology involving human identity testing is a very useful tool in the investigation of these types of events. Funding: None Disclosures: None